Economic Openness to Globalization for the Middle East and North Africa - (:unkn) unknown (My University, 2019)
Studying the factors affecting growth for Middle East and North African countries in a context of globalization imply taking into account the effects of trade openness, financial openness, specialization and the quality of institutions as main determinants of growth. In following this purpose, we studied the effect of financial development which is sensitive to quality of institutions and contingent to degree of financial openness of a country. As well as financial openness, trade openness could be an important factor for growth especially for developing countries. Therefore, free trade implies the need for specialization in a set of products and services for which a country has an advantage over its trading partners. Finally, combined financial openness and trade openness are likely to be more effective in stimulating growth according to the hypothesis of Rajan and Zingales (2003) that we propose to test for the Middle East and North African countries.
Keywords: African Research